2019
DOI: 10.1088/1742-6596/1273/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of the Vocational School Teacher Candidates’ Employability Skills

Abstract: The qualified teacher candidate of vocational schools (SMK) can be defined as individuals who have met the demands of Vocational Schools and the industry, such as mastering the hard skills and employability skills. Employability skills are the basic skills of every worker in adapting to the workplace. The purpose of this study is to describe the employability skills which must be trained to the candidates of the vocational school teacher. The results of the study showed the description of the employability ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…When instructors have better teaching performance, students tend to have higher satisfaction [39]. The extent to which teachers and students can interact and communicate well with each other has been considered critical to the success of online learning [40].…”
Section: Discussionmentioning
confidence: 99%
“…When instructors have better teaching performance, students tend to have higher satisfaction [39]. The extent to which teachers and students can interact and communicate well with each other has been considered critical to the success of online learning [40].…”
Section: Discussionmentioning
confidence: 99%
“…Later, empirical research among 916 college students in South Korea supported this positive relationship between digital literacy and perceived employability (Kim, 2020). Positive attitude is one important aspect of soft skills confirmed to affect undergraduate employability positively (Majid et al, 2019;Yudiono and Budiman, 2019). Additionally, there is a design in Indonesia that confirmed that knowledge sharing as a framework of Inquiry-Based Expertise Sharing enhanced graduate employability (Noperman et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Learning media should be attract to study the students. Interesting learn media also can stimulated spirit study the students, so that the learning process becomes more maximal and the quality of learning in the classroom can be further improved (Hadromi et al, 2019). (Widodo & Wahyudin, 2018) concluded that learning media is a device used by teachers to send information for students.…”
Section: Introductionmentioning
confidence: 99%